Poster — Thur Eve — 26: Evaluation of lens dose from anterior electron beams: comparison of Pinnacle and Gafchromic EBT3 film - Sanier, M; Wronski, M; Yeboah, C (Medical physics (Lancaster), 2014)
The purpose of this work is twofold: 1) to measure dose profiles under lead shielding at the level of the lens for a range of clinical electron energies via film dosimetry; and, 2) to assess the validity of the Pinnacle treatment planning system (TPS) in calculating the penumbral doses under lead shielding with the heterogeneous electron algorithm. First, a film calibration curve that spanned the electron energies of interest, 6–18MeV, was created. Next, EBT3 film and lead shielding were incorporated into a solid water phantom with the film positioned 7mm below the lead and a variable thickness of bolus on top. This geometry was reproduced in the Pinnacle TPS and used to calculate dose profiles using the heterogeneous electron algorithm. The measured vs. calculated dose profiles were normalized to dmax in a homogeneous phantom with no lead shielding and compared. Pinnacle consistently overestimated the dose distal to the lead shielding with significant discrepancies occurring near the edge of the lead shield reaching 25% at the edge and 35% in the open field region. The film measurements showed that a minimum lead margin of 5mm extending beyond the diameter of the lens is required to adequately shield the lens to ≤10% of the dose at dmax. These measurements allow for a reasonable estimate of the dose to the lens from anterior electron beams. They also allow for clinicians to assess the extent of the lead margin required to reduce the lens dose to an acceptable amount prior to radiotherapy treatment.